Polyurethane/Poly(2-(Diethyl Amino)Ethyl Methacrylate) blend for drug delivery applications - Echeverría, María Gabriela (2015)
A pH-sensitive blend of polyurethane (PU) and poly(2-(diethyl amino)ethyl methacrylate (PDEA) with good film‑forming capacity was prepared from the corresponding aqueous dispersions. The polymer matrix was first characterized by using FTIR, DSC, water vapor transmission and water swelling capacity at different pHs. The drug release profile of films was evaluated using a vertical Franz Cell and theophylline as model drug. The water swelling degree increases from 54 to 180% when the pH of the medium is changed from 6 to 2, demonstrating the pH-responsive behavior of the film. The in-vitro release studies indicate that an anomalous transport mechanism governs the theophylline release.